Exploration, Collection & Characterization of Genetic Diversity of Chironji (Buchnania lanzan) through Use of Morphological Analysis in Chhattisgarh, India - Chaitali Niratker (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
In the present study, Exploration, Collection & Characterization of genetic diversity of Chironji through use of the morphological analysis from Chhattisgarh was studied on the basis of seed. Conservation and sustainable use of this type of species is an important necessity for ecologically sustainable development, food security and development of socio-economically poor communities of the nation. Buchanania lanzan Spreng, commonly known as Chironji, belongs to family Anacardiaceae This significant non-woody tree species is found in Northern, Western, and Central India’s deciduous regions, primarily in the states of Madhya Pradesh, Jharkhand, and Chhattisgarh. Currently, it grows in forests as an underutilized fruit that provides a monitory reward to the nation’s tribal group and appears to be a benefit for them. It is a highly heterozygous plant so lots of variation to study. In present research, from three agro climatic zones total 27 wild Chironji genotypes with three replicates of nine trees were selected for the study of six Morpho-Physiological attributes in all of Chhattisgarh. Analysis of variance showed highly significant differences for all characters. Comparative study of all characters among the provenances revealed zone - 1 Bastar plateau zone with more vigorous growth of seeds and better survival rate for those from Raipur plane and Northern Hill. This may constitute better materials for afforestation. Furthermore, this variability appeared to be geographically structured so these results should be helpful for afforestation of Chironji. This study provides a roadmap for researchers to identify specific traits that are genetically controlled, heritable, and offer potential for meaningful genetic improvement.